Multi-Aspect Incremental Tensor Decomposition Based on Distributed In-Memory Big Data Systems - Yang Hye-Kyung; Yong Hwan-Seung (Journal of Data and Information Science, 2020)
We propose InParTen2, a multi-aspect parallel factor analysis three-dimensional tensor decomposition algorithm based on the Apache Spark framework. The proposed method reduces re-decomposition cost and can handle large tensors.